High‐Resolution Potassium Observations of the Lunar Exosphere. Issue 12 (17th June 2019) - Rosborough, S. A.; Oliversen, R. J.; Mierkiewicz, E. J.; Sarantos, M.; Robertson, S. D.; Kuruppuaratchi, D. C. P.; Derr, N. J.; Gallant, M. A.; Roesler, F. L.
Abstract: We observed lunar exospheric potassium D1 (7, 698.9646 Å) emissions using a high‐spectral resolution Fabry‐Perot spectrometer in 2014. We present the first potassium line profile measurements, which are representative of the potassium velocity distribution. Inferred temperatures are greater during the waxing gibbous phase, 1920±630 K and lower at waning gibbous phase, 980±200 K. Exosphere models suggest that the measured line widths are a combination of photon‐stimulated desorption and impact vaporization sources. The relative potassium emission intensity decreases by ∼2.5 between lunar phases 80° and 30° and is brightest off the northwest limb near the Aristarchus crater, which is a potassium‐rich surface region. Additionally, the emissions off the northern limb are brighter than the southern limb. The intensity decrease and the greater line width during the waxing gibbous versus the waning gibbous phase suggests a dawn‐dusk asymmetry. Plain Language Summary: Potassium is one of the constituents in the rarefied but measurable lunar atmosphere. Although not the most abundant element, it can be observed spectroscopically from Earth and can be used to understand processes that are responsible for sustaining the lunar atmosphere. We present the first atmospheric potassium data set of ground‐based observations to cover several months and the first potassium line profile measurements. We analyze potassium in the Moon's atmosphere in terms of temperature and intensity as it relates to the lunar phase. The potassium temperature during waxing phases is approximately 2 times hotter than the temperature during the waning phases, creating a noticeable asymmetric pattern. The potassium intensity gradually decreases as the Moon gets brighter until the emission signal is lost in scattered moonlight then increases again with time after full Moon. Data near surface regions known to be rich in potassium have higher intensities in the atmosphere than at other locations. Studying temperature and intensity patterns combined with future modelling gives insight to the processes regulating the Moon's atmosphere. Key Points: The average potassium effective temperature is 1920 +/‐ 630 K and 980 +/‐ 200 K for waxing and waning gibbous phases, respectively The relative intensity curve suggests that the source rate decreases more rapidly with local time for waxing than waning phases The relative intensity is affected by location, being brightest above potassium‐rich KREEP soils